The caring entrepreneur? Childcare policy and private provision in an enterprising age - Gallagher AM (PION LTD)
Childcare has become a recent focus of government intervention. Concerns have been raised about the soaring costs for parents, patchy provision, and the often small and unprofitable nature of the services themselves. This paper will explore how the problem of sustainability in the childcare sector is being addressed through a neoliberal development rationale. Focusing on the Irish childcare sector and the childcare funding programme introduced in 2006, I will illustrate how a particular entrepreneurial subjectivity has been mobilised to remedy the perceived problems of private sector childcare. I refer to this subjectivity as the ‘caring entrepreneur’. After I outline the contours of this subjectivity, the final section of the paper will examine how it is being realised within a rural childcare market, in the process offering a more situated account of what ‘sustainability’ means in place.
Keywords: Science & Technology; Social Sciences; Life Sciences & Biomedicine; Environmental Studies; Geography; Environmental Sciences & Ecology; childcare; subjectivity; entrepreneurship; place; Ireland; WOMEN BUSINESS OWNERS; WELFARE-REFORM; WORK; GENDER; GOVERNMENTALITY; NEOLIBERALISM; UK; PARTNERSHIPS; GEOGRAPHIES; PARENTS; 1205 Urban and Regional Planning; 1402 Applied Economics; 1604 Human Geography